2015
DOI: 10.3906/sag-1310-5
|View full text |Cite
|
Sign up to set email alerts
|

Structural chromosomal abnormalities in couples with recurrent abortion in Egypt

Abstract: Background/aim: To evaluate the incidence of chromosomal abnormalities in couples who experience recurrent abortion and identify additional factors that may be predictive of abortion, such as parental age and unfavorable obstetric or abnormal semen analysis. Materials and methods:The present study examined 125 couples who had experienced recurrent abortion. All subjects provided a detailed personal medical history and ancestral history and underwent a physical examination. Women in the study group underwent bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…An increased tendency to early miscarriages in familial pericentric inversions has been well documented [26]. Table 2 shows that the distribution of structural chromosomal rearrangements in our study is similar to that reported worldwide Table 4 [27].…”
Section: Discussionsupporting
confidence: 87%
“…An increased tendency to early miscarriages in familial pericentric inversions has been well documented [26]. Table 2 shows that the distribution of structural chromosomal rearrangements in our study is similar to that reported worldwide Table 4 [27].…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, we identified that 69 couples (11.00%) had chromosomal abnormalities. This frequency is comparable to that reported in Iran (11.68%) [15], Italy (9.66%) [16], the Netherlands (9.46%) [16], Sultanate of Oman (8.68%) [17], Switzerland (7.29%) [16], Saudi Arabia (7.10%) [18,19], Egypt (6.40%) [20], Mexico (5.83%) [16,21], Belgium (5.34%) [22], Pakistan (5.33%) [23], Argentina (5.28%) [24], Brazil (5.09%) [25], the Philippines (5.06%) [26], India (4.90%) [27][28][29], Japan (4.54%) [30], Turkey (4.21%) [16,31], France (4.14%) [16], Tunisia (4.07%) [32], and the UK (3.52%) [33]. But it is significantly higher than that identified in China (2.98%, P = 0.048) [34] and in the USA (2.96%; P = 0.048) [35].…”
Section: Discussionsupporting
confidence: 85%
“…However, samples with the aforementioned disorders that may injure the fetal brain structures had been excluded (Waldorf and McAdams, 2013). Fetal chromosomal abnormality, on the other hand, may cause significant congenital anomalies and mental retardation in infant, if the pregnancy continues to term (Gaboon et al, 2015). However, 3.0 T MR pre-scanning had been conducted by pediatric neuro-radiologist to ensure that the developmental status of the brain structures, such as the size of the cerebrum, developmental status of cerebral cortex, lateral ventricle, and corpus callosum, was anatomically normal.…”
Section: Discussionmentioning
confidence: 99%